MOSQUE-BASED EMPOWERMENT THROUGH CORPORATE SOCIAL RESPONSIBILITY FUNDS (CASE STUDY OF UMMAD ACTION PROGRAM) - Nurendahsari Gunawan; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to understand the implementation of mosque-based empowerment through CSR (Corporate Social Responsibility) funds in improving the economic benefit of the people around the mosque. This study uses a qualitative approach with an exploratory case study strategy. The object of this study is Ummad Action Program, which was initiated in 2017 by the Financial Services Authority (OJK). The results of this study are that each partner knows and agrees with the background, goals, and benchmarks of program success. However, each partner has not been optimal in carrying out their duties and responsibilities. Moreover, the success of the Ummad Action Program can be assessed in terms of the benefits felt by the congregation, including the category of success with several evaluations.Keywords: Empowerment, Corporate Social Responsibility, Mosque, Financial Services Authority (OJK).REFFERENCE Al-Quran dan Terjemahannya. (2015). Jakarta: Departemen Agama Republik Indonesia.Badan Pusat Statistik Kota Surabaya. Statistik Daerah Kota Surabaya (2018). Katalog: 1101002.3578 https://surabayakota.bps.go.id/publication/2018/10/29/d9795f386e95ea222325f428/statistik-daerah-kota-surabaya-2018.html Diakses pada 21 April 2019__________. Berita Resmi Statistik: Profil Kemiskinan di kota Surabaya tahun 2018.  https://surabayakota.bps.go.id/pressrelease/2018/12/26/119/profil-kemiskinan--di-kota-surabaya-tahun-2018.html Diakses pada 21 April 2019Erna, Setijaningrum. (2017). Program terpadu penanggulangan kemiskinan di Kota Surabaya. Masyarakat, Kebudayaan dan Politik, 30(1), 13-19.Hasyim, Sukarno L. (2016). Strategi masjid dalam pemberdayaan ekonomi umat. Jurnal Lentera, 14(2), 279-290.Hidayat, Abdul Rahman. (2013). Strategi pengembangan masjid sebagai baitul maal dalam pemberdayaan lingkungan masyarakat sekitar melalui program i-masjid ICMI pada yayasan masjid al muhajirin di Gresik. Tesis tidak diterbitkan. Surabaya: Program Pasca Sarjana Universitas Airlangga.Istan, Muhammad. (2017). Pengentasan kemiskinan melalui pemberdayaan  ekonomi umat menurut persfektif Islam. Al Falah: Journal of Islamic Economics, 2(1), 81-99.Muslim, Azis dan Ravik Karsidi. (2014). A mosque-based  economic empowerment model for urban poor comunity. International Jounal of Social Research, 2(2), 80-93.Sanrego, Yulizar D dan Moch Taufik. (2016). Fiqih tamkin (fiqih pemberdayaan) membangun modal sosial dalam mewujudkan khairu ummah. Edisi Pertama. Jakarta: Qisthi Press.Suryani, Husniyah dan Siti Inayatul Faizah. (2015). Peran masjid sebagai roda penggerak perekonomian masyarakat (penelitian deskriptif pada PKL di kawasan masjid Al-Akbar Surabaya). Jurnal Ekonomi Syariah Teori dan Terapan, 2(5), 387-399.Tim Pengembangan Keuangan Syariah Kantor OJK Regional 4 Jawa Timur. (2017). Handbook: Akses keuangan syariah untuk masyarakat mandiri berbasis masjid. Surabaya: Otoritas Jasa Keuangan (OJK).Yin, Robert K. (2015). Studi kasus design dan metode. Jakarta: Raja Grafindo Persada.